2017
DOI: 10.4309/jgi.v0i34.3963
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Five-Factor Personality Domains to Gambling Motives in Emerging Adult Gamblers: A Longitudinal Study

Abstract: At least three types of gambling motives have been proposed: coping motives (gambling to reduce negative affect), enhancement motives (gambling to enhance positive affect), and social motives (gambling to increase social affiliation). Few studies have examined the underlying personality traits that give rise to these different motivations. The present study tests the longitudinal link between changes in five-factor model personality domains and gambling motives among emerging adults. A sample of 679 emerging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The three motives are defined as "Coping", which is related to relieving negative affect, "Enhancement", which is related to strengthening positive affect, and "Social", which is related to strengthening social connections. extraversion was associated with enhancement and social motives and agreeableness was related to social and coping motives in young adults (Mackinnon, Lambe, & Stewart, 2016). Despite these connections in young adult and older samples, no work to date has investigated how gambling motives may fit into the landscape of personality, sensation-seeking, and gambling problems in adolescents.…”
Section: Personality and Gambling Motivesmentioning
confidence: 97%
“…The three motives are defined as "Coping", which is related to relieving negative affect, "Enhancement", which is related to strengthening positive affect, and "Social", which is related to strengthening social connections. extraversion was associated with enhancement and social motives and agreeableness was related to social and coping motives in young adults (Mackinnon, Lambe, & Stewart, 2016). Despite these connections in young adult and older samples, no work to date has investigated how gambling motives may fit into the landscape of personality, sensation-seeking, and gambling problems in adolescents.…”
Section: Personality and Gambling Motivesmentioning
confidence: 97%
“…In addition, MacLaren, Ellery, and Knoll ( 2015 ) reported that the relationship between aspects of conscientiousness (i.e., low industriousness) and gambling severity was mediated through coping motives. In the most comprehensive test, Mackinnon, Lambe, and Stewart ( 2016 ) investigated relationships between FFM traits and gambling motives using a longitudinal data set of young adult gamblers. Their analyses revealed positive associations between extraversion scores and both enhancement and social motives; whereas, low agreeableness was linked to lower social and coping scores.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on personality and gambling has focused on FFM characteristics in gambling severity (e.g., Bagby et al., 2007 ; Brunborg et al., 2016 ; MacLaren et al., 2011 ). Moreover, only one study (i.e., Mackinnon et al., 2016 ) explored associations between FFM traits and GMQ motives. Research on the utility of HEXACO in addiction is limited.…”
Section: Introductionmentioning
confidence: 99%